2018
DOI: 10.1080/1461670x.2018.1499436
|View full text |Cite
|
Sign up to set email alerts
|

Cornerstones in Journalism

Abstract: Journalism's appeal to the public is in decline and the causes and remedies for this are debated in society and academia. One dimension that has garnered attention is that of journalistic norms and how they are performed; it has been proposed that a journalism based on a different, more transparent, normative base can better connect with citizens, compared with the current prevailing norm of journalistic objectivity. However, the opinions of citizens themselves have been remarkably absent and, in order to info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
2
21
1
Order By: Relevance
“…These are the conclusions drawn from a study based on a survey answered by 3,203 Dutch citizens (van der Wurff & Schönbach, 2014). Other studies that have reflected the opinion of citizens have agreed with this critical view, pointing out that more than the validity of the rules themselves, the problem lies in the interpretation that journalists make of them or, more specifically, in the way they put them into practice (Craft, Vos & Wofgang, 2016;Karlsson & Clerwall, 2019). Meanwhile, other research carried out in the United States offers a more positive view, although citizens' perception is lower than that of the professionals themselves (Gil de Zuñiga & Hinsley, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 90%
See 1 more Smart Citation
“…These are the conclusions drawn from a study based on a survey answered by 3,203 Dutch citizens (van der Wurff & Schönbach, 2014). Other studies that have reflected the opinion of citizens have agreed with this critical view, pointing out that more than the validity of the rules themselves, the problem lies in the interpretation that journalists make of them or, more specifically, in the way they put them into practice (Craft, Vos & Wofgang, 2016;Karlsson & Clerwall, 2019). Meanwhile, other research carried out in the United States offers a more positive view, although citizens' perception is lower than that of the professionals themselves (Gil de Zuñiga & Hinsley, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 90%
“…Finally, we aim to find out what citizens think about the different accountability instruments. The opinion of citizens has already been gathered in other reference studies which have used various methodologies, such as discussion groups (Karlsson & Clerwall, 2019), content analysis of public comments (Craft, Vos & Wofgang, 2016) or online questionnaires (Gil de Zuñiga & Hinsley, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While journalism as a profession is apparently in a state of disruption, the (often implicit) meaning and limits of quality remained fairly constant over the years (cf. Ahva and Steensen 2020; Karlsson and Clerwall 2019;Lacy and Rosenstiel 2015). In short, the question may not be why the boundaries of journalism discourse are shifting or getting blurred (cf.…”
Section: Analytical Approachmentioning
confidence: 99%
“…It was also found that the online media does not pose any challenge to the mainstream media. This was collaborated by the Karlsson and Clerwall, (2019) who argue that a remedy to the decreasing trust in news may not be blamed on the changing of norms in journalism brought by online media, but rather on how the already established norms and values of the journalistic professions are performed. Yamamoto, and Nah, (2018) found that as structural pluralism is negatively related to local newspaper credibility, conservative ideology, newspaper use, social trust, and political trust are significantly related to local newspaper credibility.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%